The Use of Samples Originating From Doping Control Procedures for Research Purposes: A Qualitative Study. (July 2019) - Devriendt, Thijs; Phillips, Amicia; Shabani, Mahsa; Borry, Pascal
Doping control samples may be used for research purposes by the World Anti-Doping Agency (WADA)-accredited laboratories after their compulsory storage period has expired. This study investigates opinions of stakeholders toward the governance of antidoping research on these samples and to evaluate the current framework. Semistructured interviews were conducted with stakeholders in antidoping research. The distinction between research and quality assurance in the International Standard for Laboratories (ISL) is neither well-understood nor interpreted uniformly by WADA-accredited labs. Most laboratories would not seek ethics approval for research on doping control samples. Interviewees considered that athletes should be better informed on what antidoping research can entail. A consistent and uniform approach toward the consent should be employed worldwide. Standards and safeguards should be implemented to reduce the risk of reidentification. Centralization of the Informed Consent Form in the ADAMS (Anti-Doping Administration & Management System) database would facilitate providing more information and allow the implementation of the right to withdraw.